Pengaruh Model Pembelajaran Kooperatif Tipe Artikulasi Terhadap Keaktifan Belajar Pendidikan Agama Kristen Siswa Kelas VIII SMP Negeri 3 Tarutung Tahun Pembelajaran 2023/2024 - Jerry Damanik; Megawati Manullang; Boho P Pardede; Tianggur Napitupulu; Dame Taruli Simamora (LPPM Politeknik Pratama, 2023)
The study aims to determine the effect of the articulation type cooperative learning model on the activeness of PAK learning of students in class VIII of SMP Negeri 3 Tarutung in the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence between the articulation type cooperative learning model on the PAK learning activeness of students in class VIII of SMP Negeri 3 Tarutung in the 2023/2024 Learning Year. The research method used is descriptive and inferential quantitative. The population of all VIII grade students of SMP Negeri 3 Tarutung in the 2023/2024 academic year who are Protestant Christians totaling 163 people. The sample was determined by simple random sampling technique (random sample) of 30% of the total population of 49 people. The research instrument was a closed questionnaire. The results of data analysis obtained: a) The value of rcount = 0.512> rtable = 0.281 and tcount = 4.086> ttable = 2.021 shows a positive and significant relationship. b) Regression equation. c) Determination test is known to be the influence of 26.21%. d) Hypothesis testing obtained Fcount = 16.568> Ftabel = 3.23 then H0 is rejected and Ha is accepted. The study concluded that there is a positive and significant influence between the articulation type cooperative learning model on the activeness of PAK learning of class VIII students of SMP Negeri 3 Tarutung in the 2023/2024 Learning Year.